Individual investor mutual fund flows☆ - Ivković, Zoran; Weisbenner, Scott (Journal of Financial Economics, 2009)
This paper studies the relation between individuals’ mutual fund flows and fund characteristics, establishing three key results. First, consistent with tax motivations, individual investors are reluctant to sell mutual funds that have appreciated in value and are willing to sell losing funds. Second, individuals pay attention to investment costs as redemption decisions are sensitive to both expense ratios and loads. Third, individuals’ fund-level inflows and outflows are sensitive to performance, but in different ways. Inflows are related only to “relative” performance, suggesting that new money chases the best performers in an objective. Outflows are related only to “absolute” fund performance, the relevant benchmark for taxes.